HOUSE SALES SYSTEM ON PT. MASA KREASI - Franky Franky; Yuce Yuliani. Skom. MM (Jurnal Sistem Informasi, 2000)
After the formation of house sales system on PT. MASA KREASI Computerized isexpected to overcome the problems faced by PT. MASA KREASI. Home sales datacollection process in PT. MASA KREASI can be faster, able to provide facilities inthe home search process data if necessary at any time.